Perbandingan Sistem Pemerintahan Nabi Muhammad Shallallahu ‘Alaihi Wasallam dan Pemerintahan Indonesia Perspektif Politik Profetik Kuntowijoyo - Lesmana, Irwan; Hidayat, Muhammad Panji; Latua, Abidin (Media Hukum Indonesia (MHI), 2025)
This study discusses the comparison between the governance system during the time of Prophet Muhammad (peace be upon him) and the governance system in Indonesia, particularly from the perspective of Kuntowijoyo’s prophetic political theory. The governance system in the Prophet’s era and modern Indonesia have fundamental differences, yet both can be comprehensively analyzed through Kuntowijoyo’s prophetic politics, which emphasizes the values of humanization, liberation, and transcendence. The Prophet’s governance was based on divine revelation, incorporating principles of consultation (shura), social justice, and respect for the diversity of the Madinah community, exercising power as a moral trust within a theodemocratic system. Meanwhile, Indonesia’s governance adopts a representative democracy with separation of powers and legitimacy derived from the people’s mandate through elections, but it still faces challenges in fully actualizing prophetic values. Therefore, political and ethical leadership reforms grounded in prophetic political principles are essential so that modern governance not only operates formally and legally but also realizes social justice and structural liberation, leading to a civilized and dignified society.